Combination of vertical axis wind turbine and solar photovoltaic for hybrid energy - Almotairi, Abdulaziz M M (2019)
One of the most inexpensive and cleanest sources of renewable energy or technology is wind energy. The emergence of a new market i.e. wind technology, has the means of efficiently converting wind energy into a usable form of energy, which is electricity. The foundation of this new technology is the wind turbine, a machine that transfers fluid energy that passes through the blades and shafts, to mechanical energy, and later transforming mechanical energy to electricity via the use of a generator. The Vertical Axis Wind Turbine (VAWT) has been a popular choice as it is quiet, small and has a simple design. Some examples of VAWT are Darrieus, Savonius, and Vane. In developing countries, VAWT is used as a suitable alternative to wind power extraction, mainly due to its advantages over the horizontal axis type, such as ease of construction, cost efficient, and capable to accept wind flows from any direction without requiring orientation. Notwithstanding these advantages, today VAWT is not gaining popularity because of the low efficiency of the Savonius type rotor and low starting torque of the Darrieus type wind machines. There is also a lack of energy harvesting for the VAWT system. The problem arises because the average wind speed is very slow. Therefore, low wind speed causes the energy harvesting to not operate efficiently. Hence, the first objective of this research is to design a VAWT by combining both the Savonius and Darrieus types so that the combination of these designs meets the expectation of having a wind turbine that performs well. Besides that, to overcome the problem of efficiency of the wind turbine, a solar photovoltaic system with solar tracking will be designed and embedded into the turbine to function as another harvesting tool in the system. Lastly, the main objective of this research is to design a solar tracking combined with photovoltaic and integrating it into the VAWT system, to maximise energy harvesting. A few concepts were generated in the conceptual design stage. The Darrieus- Savonius VAWT design can be suitably placed in a built environment where it can harness more power from wind and at the same time, is also able to self start in low wind conditions prevalent in such environment. The study shows improvements in the power coefficient and efficiency for the Savonius-Darrieus wind turbine in comparison with the use of the Savonius wind turbine and Darrieus wind turbine only. The results showed the start-up speed and rotation of the Savonius-Darrieus wind turbines is the best design of VAWT, as it has a good start-up speed and rotation which enables it to generate electricity more efficiently. The weighted objective method is then used to finalise the most suitable design and the dual axis solar tracking system is defined, before proceeding with the next step. When the dual axis solar tracking system is built up, it is able to track with the light source and make adjustments on the tilt base for the PV to harvest solar energy. This dual axis tests are to prove the functionality and response towards the DC and servo motors. Finally, this research will emphasise the integrated design of solar photovoltaic embedded in a solar tracking system to ensure maximum energy harvest.